100 Cartas para Paulo Freire de quienes pretendemos Enseñar - Gárate Vergara, Francisco (Ariadna Ediciones, 2021)
Tribute book to Paulo Freire on the centenary of his birth. There are 100 letters made by educators from all over Latin America and other parts of the world. The contribution and value of Freire's pedagogical work and its validity in the current context of our countries are recognized.